The secondary structure and sequence optimization of an RNA ligase ribozyme. - Ekland, E H (1995)
In vitro selection can generate functional sequence variants of an RNA structural motif that are useful for comparative analysis. The technique is particularly valuable in cases where natural variation is unavailable or non-existent. We report the extension of this approach to a new extreme--the identification of a 112 nt ribozyme secondary structure imbedded within a 186 nt RNA. A pool of 10(14) variants of an RNA ligase ribozyme was generated using combinatorial chemical synthesis coupled with combinatorial enzymatic ligation such that 172 of the 186 relevant positions were partially mutagenized. Active variants of this pool were enriched using an in vitro selection scheme that retains the sequence variability at positions very close to the ligation junction. Ligases isolated after four rounds of selection catalyzed self-ligation up to 700 times faster than the starting sequence. Comparative analysis of the isolates indicated that when complexed with substrate RNAs the ligase forms a nested, double pseudo-knot secondary structure with seven stems and several important joining segments. Comparative analysis also suggested the identity of mutations that account for the increased activity of the selected ligase variants; designed constructs incorporating combinations of these changes were more active than any of the individual ligase isolates.